Thermally conductive electro-osmotic propulsive pressure-driven peristaltic streaming flow study with a suspended nanomaterial in a micro-ciliated tube - Butt, Adil Wahid; Akbar, Noreen Sher; Mehmood, Rashid; Farooq, Shahid (Frontiers in Materials, 2022)
This article focuses on the peristaltic flow of carbon nanoparticle-suspended nanofluids under the influence of electroosmosis. The flow is considered inside a vertical tube with ciliated boundary walls. This study holds great importance because it represents the flow inside the esophagus of the human body. Nanoparticles are inserted in blood for diagnosing diseases like cancer and are also useful in angiography, angioplasty, etc. A comparative study is conducted for single-walled carbon nanotubes and multi-walled carbon nanotubes. We used the analytical method to obtain exact solutions of the velocity, temperature, and pressure profiles. The results have been presented graphically. Streamlines are also plotted to visualize the difference with SWCNT and MWCNT. We found that the use of CNT in the base fluid significantly enhances the thermal conductivity and helps increase the velocity of the fluid.